Storyteller - Underwood, Carrie (Nashville, TN Arista, 2015)
Country superstar Carrie Underwood is back with her fifth album, her first since 2012's chart-topping Blown Away. It includes her latest hit single Smoke Break.
Renegade runaway (3:38) -- Dirty laundry (3:24) -- Church bells (3:13) -- Heartbeat (3:30) -- Smoke break (3:18) -- Choctaw County affair (3:29) -- Like I'll never love you again (3:36) -- Chaser (4:22) -- Relapse (3:23) -- Clock don't stop (3:21) -- The girl you think I am (3:37) -- Mexico (3:27) -- What I never knew I always wanted (3:33).
Title from disc label.
Lyrics and full credits on container insert.
Performed by Carrie Underwood ; with accompaniment.
Keywords: Country music -- 2011-2020.; Popular music -- 2011-2020.